Molecular dynamics simulation of nanoindentation on c-plane sapphire. (March 2021) - Lin, Jiaming; Jiang, Feng; Xu, Xipeng; Lu, Jing; Tian, Zige; Wen, Qiuling; Lu, Xizhao
Abstract: Sapphire is a typical hard and brittle material, making it difficult to investigate its plastic deformation behavior using conventional mechanical experimental methods. Although nanoindentation and transmission electron microscopy (TEM) have been used to characterize its plastic deformation behavior, the dynamic deformation process remains difficult to observe, which limits our understanding of the mechanism of plastic deformation in sapphire. In this study, the plastic deformation mechanism of c -plane (0001) sapphire under nanoindentation was simulated using the molecular dynamics (MD) method. The relationship between the surface morphology of the nano-indented c -plane sapphire and the activation process of slip systems was studied. The simulation results are in good agreement with the nanoindentation experiment results. A hexagonal pattern was induced on the indented surface of c -plane sapphire by prismatic slip activation. A three-fold symmetry pile-up was observed because of rhombohedral slip activation, and the twin/slip systems of the r -plane and a -plane provided a nucleation condition for crack formation on c -plane sapphire in the experiments. In addition, the MD simulation results showed that the O atomic arrangement transforms from an HCP structure to an FCC structure, mostly between the two basal dislocation lines. This change in the arrangement of O atoms is attributed to the basal dislocations in sapphire. The study is expected to broaden our understanding of the deformation mechanism in c -plane sapphire and to help facilitate its analysis on a nanometer-scale. Highlights: The nanoindentation process of sapphire is simulated by molecular dynamics method. The activation of twin/slip system has an important influence on the sapphire indentation morphology. Basal slip of sapphire results in the change of oxygen atom arrangement structure. The relationship between plastic deformation and fracture of sapphire is investigated.